Evaluation of Mutiara Strain Catfish Seed Production (Clarias sp.) at UPR Farm 169 Kubu Raya, West Kalimantan - Khairah, Hylda; Wahyudin, Wahyudin; Effendi, Irzal (Jurnal Media Akuakultur Indonesia, 2025)
Mutiara catfish is one of the leading commodities in the freshwater fish farming sector in Indonesia. Catfish has the advantage of good meat quality, a fast growth rate, and can live at high density. The continuous availability of seeds is one of the key factors in meeting the demand for catfish seeds in West Kalimantan. This study aims to evaluate the catfish seed production system at Farm 169, Kubu Raya, West Kalimantan. The seeding process includes pond preparation, parent selection, spawning, egg hatching, larval maintenance and harvesting, feeding, and water quality management. The results of the fecundity calculation of pearl catfish obtained the number of eggs as many as 142.200, fertilization rate of 85.08%, hatching rate of 83.12%, and larval survival rate of 92.62%.